2021
DOI: 10.3390/nu13103592
|View full text |Cite
|
Sign up to set email alerts
|

Choice Architecture Cueing to Healthier Dietary Choices and Physical Activity at the Workplace: Implementation and Feasibility Evaluation

Abstract: Redesigning choice environments appears a promising approach to encourage healthier eating and physical activity, but little evidence exists of the feasibility of this approach in real-world settings. The aim of this paper is to portray the implementation and feasibility assessment of a 12-month mixed-methods intervention study, StopDia at Work, targeting the environment of 53 diverse worksites. The intervention was conducted within a type 2 diabetes prevention study, StopDia. We assessed feasibility through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 89 publications
(152 reference statements)
0
15
0
Order By: Relevance
“…We rolled out a one-year hybrid type 2 implementation-effectiveness trial, StopDia at Work, between 2017 and 2019 in natural settings at workplaces from three regions of Finland (Northern Savo, South Karelia, and Päijät-Häme) [ 31 ]. The intervention aimed to promote healthy dietary choices and daily physical activity with subtle modifications to the worksite choice architecture.…”
Section: Methodsmentioning
confidence: 99%
“…We rolled out a one-year hybrid type 2 implementation-effectiveness trial, StopDia at Work, between 2017 and 2019 in natural settings at workplaces from three regions of Finland (Northern Savo, South Karelia, and Päijät-Häme) [ 31 ]. The intervention aimed to promote healthy dietary choices and daily physical activity with subtle modifications to the worksite choice architecture.…”
Section: Methodsmentioning
confidence: 99%
“…However, the consumption of healthier nutrition-labelled products did not change during the intervention in either study group. Rantala et al (2022) reported a reduction of 15-24 g/customer in the absolute consumption of salad bar items, warm meals, and condiments in the self-serving lunch buffet among Finnish adults after Heart Symbol posting. Although the results of Rantala et al are in line with those of our study, they are not entirely comparable because the data collection methods and product category classifications used in their study differed from ours.…”
Section: Key Findingsmentioning
confidence: 99%
“…Lastly, it would be remiss of us to not mention StopDia at Work by Rantala et al (15), a 12-month intervention targeting the environment of diverse worksites aimed at encouraging healthier eating and physical activity. In it, they listed 53 practical strategies (aka nudges) for creating healthy work environments focused on both healthy eating and physical activity (15). Some of our favorites include placing food physically closer to the individual, using larger tongs and spoons for healthy foods and smaller tongs and spoons for less healthy foods, leaving height-adjustable desks in the upright position at the end of the day, slowing down elevator doors to encourage stair use (this one made us chuckle), and posting an attention-getting story or riddle that leads to the stairs from the point-of-choice between the stairs and the elevator (oh, how we love a good riddle) (15).…”
Section: Health-promoting Nudge Effectivenessmentioning
confidence: 99%
“…Point-of-choice prompts have been popular and shown to be effective in increasing physical activity, with stair-use interventions most often studied (13,14). Lastly, it would be remiss of us to not mention StopDia at Work by Rantala et al (15), a 12-month intervention targeting the environment of diverse worksites aimed at encouraging healthier eating and physical activity. In it, they listed 53 practical strategies (aka nudges) for creating healthy work environments focused on both healthy eating and physical activity (15).…”
Section: Health-promoting Nudge Effectivenessmentioning
confidence: 99%